Entrepreneurıal Orıentatıon In The Context Of Innovatıon And Dıgıtal Fınancıal Inclusıon For Msmes - Restu Millaningtyas; Heri Pratikto; Ludi Wishnu Wardana (Cita Konsultindo Research Center, 2024)
The Covid-19 pandemic has become a major challenge for the business world, increasing the use of technology including fiscal technology services, MSMEs that are connected in the digital ecosystem have better resilience and the Indonesian government emphasizes the importance of Digital Financial Inclusion in MSME financing to reduce gaps due to global uncertainty as a result of the pandemic and geopolitical conditions. Digitalization of Financial Inclusion can spearhead the success of MSMEs, so a strong entrepreneurial orientation is needed, Entrepreneurial orientation is the ability possessed by business actors to identify and take advantage of business opportunities through innovation and measurable risk taking for business growth. The method used in this article is Systematic Literature Review using PRISMA diagrams with 41 articles aligned with creteria. The result of this review article is that MSMEs with opportunity identification, ease of financial technology and appropriate technology are very easy to get opportunities to develop, manage risks and dare to take risks by continuing to adapt to digital inclusion both capital, financing and transactions and continue to innovate sustainably will make it easier for MSMEs to be able to improve performance and contribute to economic growth.